ANALYSIS OF THE GENERAL DIRECTORATE OF SPORTS SERVICES OF THE FIVE-YEAR BUDGET IN THE LIGHT OF MANAGEMENT ACCOUNTING PRINCIPLES - Kibritci, Kübra; Bayansalduz, Mehmet (Acta Scientiae et Intellectus, 2024)
The state has undertaken the management and administration of sports in Turkey. The State has given this responsibility to the General Directorate of Sports Services with the Law No. 3289. The General Directorate of Sports Services fulfills the duties and responsibilities given to it by law, in line with the opportunities provided by the general budget appropriations. In the decision-making process by the management, management accounting can be applied at three points: focusing, keeping financial data and problem solving. Each activity carried out in a calendar year shapes the future of the General Directorate of Sports Services. In the execution of the activities of the General Directorate of Sports Services, many decisions are taken, implemented and feedback is provided at almost every management level. This cycle, which is included in the General Directorate of Sports Services, requires tools with certain features, whose implementation stages can be arranged in accordance with the interests of the General Directorate of Sports Services, and that can offer results comparable to other periods and/or businesses. Financial analyzes and evaluations were made based on the data of 5 years (2013, 2014, 2015, 2016, 2017) from the annual activity reports published publicly in the visual and written media after passing the audit of the General Directorate of Sports Services by the Court of Accounts.